2007
DOI: 10.1159/000112917
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Human Papillomavirus Type 18 P105 Promoter by the Co-Activator CBP

Abstract: Human papillomaviruses (HPVs) are the etiological agents of cervical cancer, with HPV-16 and 18 being the representative types of the higher risk group. The expression of the viral genes with transforming activity (E6 and E7) is controlled by the upstream regulatory region (URR), a segment of the viral genome that contains elements recognized by several transcription factors. Objective: We have analyzed the participation of the cellular co-activator CBP on the transcriptional regulation of the HPV-18 URR. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…CBP/p300 can also bind to the HPV18 URR in the absence of E2 as recruitment has been demonstrated in E2-negative cervical cancer cells [43]. CBP/ p300-dependent E6/E7 transcription activation is associated with acetylation of H3 at the HPV URR providing evidence that CBP/p300 activates HPV transcription by altering the epigenetic status of the viral enhancer/promoter [44]. Increased histone acetylation by CBP/p300 results in enhanced recruitment of the SWI/SNF chromatin remodelling complex catalytic subunit, the Brahma-related gene-1 (Brg1), to the URR which is required for efficient RNA polymerase II recruitment [45].…”
Section: Histone Acetylationmentioning
confidence: 81%
“…CBP/p300 can also bind to the HPV18 URR in the absence of E2 as recruitment has been demonstrated in E2-negative cervical cancer cells [43]. CBP/ p300-dependent E6/E7 transcription activation is associated with acetylation of H3 at the HPV URR providing evidence that CBP/p300 activates HPV transcription by altering the epigenetic status of the viral enhancer/promoter [44]. Increased histone acetylation by CBP/p300 results in enhanced recruitment of the SWI/SNF chromatin remodelling complex catalytic subunit, the Brahma-related gene-1 (Brg1), to the URR which is required for efficient RNA polymerase II recruitment [45].…”
Section: Histone Acetylationmentioning
confidence: 81%
“…The CBP/p300 chromatin modulator is further recruited by the HPV18 enhanceosome to stimulate the promoter activity [92]. The activation of the HPV18 P105 promoter by the coactivator CBP directly correlates with the induction of the nucleosomal histone H3 (K14) acetylation on the HPV18 Early Promoter by CBP [93]. Brm is a chromatin remodeling protein associated with SWI/SNF complexes, which are ATP-dependent chromatin remodeling enzymes.…”
Section: Cellular Factors Involved In Viral Chromatin Remodelingmentioning
confidence: 99%
“…Bernat et al demonstrated using GST pull-down assays that high-risk HPV16 E7, and to a lesser extent, low-risk HPV11 E7 directly interact with p300 in vitro [47]. Using co-immunoprecipitation and mammalian two-hybrid assays, these authors also showed that HPV16 E7 interacts with p300 in vivo [48]. Additionally, they found that HPV16 E7's interaction with p300 is necessary to inhibit p300's ability to co-activate E2-driven transcription [47].…”
Section: Histone Acetylationmentioning
confidence: 99%
“…Additionally, they found that HPV16 E7's interaction with p300 is necessary to inhibit p300's ability to co-activate E2-driven transcription [47]. CBP mediates H3K14 acetylation and upregulates the transcriptional activity of the HPV18 URR [48]. HPV16 E7 associates with histone deacetylases HDAC1 and HDAC2 indirectly through Mi2β, a member of the nucleosome remodeling and histone deacetylation (NURD) complex [49,50], and this association is independent of Rb binding [50].…”
Section: Histone Acetylationmentioning
confidence: 99%